2020
DOI: 10.1038/s41598-020-72871-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal melanism explains macroevolutionary variation of dorsal pigmentation in Eurasian vipers

Abstract: Colouration may endorse thermoregulatory and antipredatory functions in snakes. The thermal melanism hypothesis predicts that dark-coloured individuals are ecologically favoured in cool climates. However, the loss of aposematic and cryptic colourations may imply high predation for melanistic snakes. Here, we used the monophyletic group of Eurasian vipers (subfamily Viperinae) to test whether an increase in the extent of dark area inside the characteristic zigzag dorsal pattern is associated to colder environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 51 publications
2
16
1
Order By: Relevance
“…Darker integuments may contribute not only to better camouflage, but also to thermoregulatory functions in colder environments (e.g., allowing the brain to reach optimal temperatures faster 46 ) and UV protection (e.g., protecting the animal from higher radiations at higher altitudes 47 ). The present results are further supported by Martínez-Freiría et al 48 who found that darker dorsal colors in European vipers are associated with cold environments. Overall, our findings on the dorsal and ventral brightness suggest that these body regions are subjected to divergent selective forces.…”
Section: Discussionsupporting
confidence: 90%
“…Darker integuments may contribute not only to better camouflage, but also to thermoregulatory functions in colder environments (e.g., allowing the brain to reach optimal temperatures faster 46 ) and UV protection (e.g., protecting the animal from higher radiations at higher altitudes 47 ). The present results are further supported by Martínez-Freiría et al 48 who found that darker dorsal colors in European vipers are associated with cold environments. Overall, our findings on the dorsal and ventral brightness suggest that these body regions are subjected to divergent selective forces.…”
Section: Discussionsupporting
confidence: 90%
“…Contrary to our expectation, given the fact that many ectothermic animals (i.e. reptiles, insects) show darker coloration at northern latitudes (Watt, 1968;Guppy, 1986;Svensson & Waller, 2013;Martínez-Freiría et al, 2020), we did not find darker opisthosoma pigmentation with increasing latitude. However, we did find a significant association of pigmentation with one environmental principal component (PC4).…”
Section: Latitudinal Variation In Adult Phenotypes and Genotypes Across Transectcontrasting
confidence: 99%
“…Regarding morphological variability, marked differences occurred in biometric, scalation and dorsal coloration traits, particularly between species and among V. monticola subspecies. Several studies addressing morphological variability in Vipera species highlighted the adaptive and plastic character of several morphological traits, as they were found varying in accordance to environmental gradients (e.g., Martínez-Freiría et al, 2009;Martínez-Freiría, Toyama, et al, 2020;Santos et al, 2014). As in previous studies using ecological modeling tools (Brito et al, 2008;Freitas et al, 2018;Santos et al, 2006), we found that V. monticola occurs across a narrower topo-climatic niche than V. latastei (Data S4), which makes the former more sensitive to extreme and stochastic changes than the later.…”
Section: Sources Of Phenotypic Variationsupporting
confidence: 77%
“…monticola subspecies. Several studies addressing morphological variability in Vipera species highlighted the adaptive and plastic character of several morphological traits, as they were found varying in accordance to environmental gradients (e.g., Martínez‐Freiría & Brito, 2013; Martínez‐Freiría et al, 2009; Martínez‐Freiría, Toyama, et al, 2020; Santos et al, 2014). As in previous studies using ecological modeling tools (Brito et al, 2008; Freitas et al, 2018; Santos et al, 2006), we found that V .…”
Section: Discussionmentioning
confidence: 99%